Voices in Psychosis Interdisciplinary Perspectives - Woods, Angela; Alderson-Day, Ben; Fernyhough, Charles (Oxford University Press, 2022)
Voices in Psychosis: Interdisciplinary Perspectives deepens and extends the understanding of hearing voices in psychosis in a striking way. For the first time, this collection brings multiple disciplinary, clinical and experiential perspectives to bear on an original and extraordinarily rich body of testimony: transcripts of forty in-depth phenomenological interviews conducted with people who hear voices and who have accessed Early Intervention in Psychosis services. Voice-hearing experiences associated with psychosis are highly varied, frequently distressing, poorly understood, and deeply stigmatized, even within mental health services. Voices in Psychosis responds to the urgent need for new ways of listening to and making sense of these experiences. The book addresses the social, clinical and research contexts in which the interviews took place, thoroughly investigating the embodied, multisensory, affective, linguistic, spatial, and relational qualities of voice-hearing experiences. The nature, politics, and consequences of these analytic endeavours is a focus of critical reflection throughout. This volume presents a collection of essays by members and associates of the Hearing the Voice project that were written in response to the transcripts. Each chapter gives a multifaceted insight into the experiences of voice-hearers in the North East of England and to their wider resonance in contexts ranging from medieval mysticism to Amazonian shamanism, from the nineteenth-century novel to the twenty-first-century survivor movement.